2016
DOI: 10.1111/cgf.12832
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Flows of Curves in Shape Space for Processing Motion of Deformable Objects

Abstract: We introduce techniques for the processing of motion and animations of non-rigid shapes. The idea is to regard animations of deformable objects as curves in shape space. Then, we use the geometric structure on shape space to transfer concepts from curve processing in R n to the processing of motion of non-rigid shapes. Following this principle, we introduce a discrete geometric flow for curves in shape space. The flow iteratively replaces every shape with a weighted average shape of a local neighborhood and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Linear subspaces have found wide application outside of deformable solid simulation, including fluids [TLP06, SSW * 13], shape deformation [vTSSH13,BvTH16], computational design [XLCB15,MHR * 16,UMK17] and sound simulation [OSG02,JBP06]. However, very small linear subspaces can have difficulty representing even moderately non-linear deformations as seen in Figure 3 jective Dynamics [BEH18] attempts to overcome this limitation by combining model reduction with the very efficient full-space approach of Projective Dynamics [BML * 14].…”
Section: Pca Onlymentioning
confidence: 99%
“…Linear subspaces have found wide application outside of deformable solid simulation, including fluids [TLP06, SSW * 13], shape deformation [vTSSH13,BvTH16], computational design [XLCB15,MHR * 16,UMK17] and sound simulation [OSG02,JBP06]. However, very small linear subspaces can have difficulty representing even moderately non-linear deformations as seen in Figure 3 jective Dynamics [BEH18] attempts to overcome this limitation by combining model reduction with the very efficient full-space approach of Projective Dynamics [BML * 14].…”
Section: Pca Onlymentioning
confidence: 99%
“…Heeren et al [40,4] propose an alternative physically-based metric on the shape space of triangle meshes that reflects the viscous dissipation required to physically deform a thin shell. Brandt et al [41] derive a discrete curve shortening flow in shape space and use it for processing animations of deformable objects. While the shape spaces study deformations of meshes with fixed connectivity, functional correspondences [42] can be used to blend [43] and analyze [44] pairs of meshes with different connectivity.…”
Section: Related Workmentioning
confidence: 99%
“…We build on their Riemannian metric. Using this metric, Brandt et al [BvTH16] suggested a scheme that largely accelerates geodesic computation in shell space by resorting to dimensionality reduction in the spatial domain. In a different development, Winkler et al [WDAH10] and Fröhlich and Botsch [FB11] used edge length and dihedral angle coordinates to represent meshes for efficiently computing interpolation paths between two given poses.…”
Section: Related Workmentioning
confidence: 99%
“…Having the notion of geodesics at hand one can easily transfer this concept to Riemannian manifolds—Beziér curves are simply generated by applying the de Casteljau algorithm with linear interpolation replaced by geodesic interpolation [PN07]. This was done in [ERS*14] for the shape space of images and in [BvTH16] for the space of shells.…”
Section: Related Workmentioning
confidence: 99%